Leverage effect and switching of market efficiency post goods and services tax (GST) imposition - Lee, Yok Yong; Yahya, Mohamed Hisham; Amin Noordin, Bany Ariffin; Selamat, Aslam Izah (Canadian Center of Science and Education, 2018)
This paper investigates the leverage effect and switching of market efficiency after the GST imposition on fee-based financial services in Bursa Malaysia and Australian Securities Exchange (ASX). The sample in this paper comprises of public listed companies for the period of one year before and after the GST imposition. GJR-GARCH is employed to evaluate the asymmetry response that is associated with the negative news shocks. To assess the effect of transactional efficiency on the informational efficiency and the structural change of time-varying volatility, SGARCH is adopted. This research reveals the presence of leverage effect in developing and developed market. The GST imposition on fee-based financial services significantly reduces the informational efficiency in Bursa Malaysia, but not in ASX. To boost the tax revenues generated from the financial sector, the policymakers in the developed markets (similar to ASX) should contemplate imposing GST on the fee-based financial services without affecting the stability of the stock market. The investors in thin markets (such as Bursa Malaysia) could forecast the stock returns of the thin market upon GST imposition on fee-based financial services.